The dynamic of returns and volatility of Malaysian listed property companies in Asian property market - Razali, Muhammad Najib (International Journal of Strategic Property Management, 2015)
This paper examines the dynamics of return and dynamic volatility across the Malaysian and pan-Asian countries’ listed property companies market over the period January 1998 to August 2012. Listed property companies’ portfolios have the potential to offer high returns and low risks for long-term investments for individuals as well as institutional investors. As such, it is important to assess the return and volatility level of the Malaysian listed property companies market in the dynamic region of pan-Asian countries. This paper uses ARCH and GARCH models to empirically examine the dynamic volatility of listed property companies in 12 pan-Asian countries. The findings revealed that for the past 14-years Malaysia experienced moderately high volatility levels in term of investment in listed property companies. This study will contribute significantly to the empirical literature on the volatility dynamics of the Malaysian property market in international real estate portfolios. In particular, the findings from the study will be useful for international investors to better understand the potential portfolio implications of investing in the Malaysian real estate market.First Publish Online: 1 Apr 2015